Can consumers bank on financial services being secure with GDPR?. Issue 6 (June 2018) - Sydekum, Ralf
Abstract : The face of finance is changing. Everywhere you look, institutions are abandoning the high street and moving to faster, more responsive 24-hour online services to meet customer demand. Yet, as digital engagement increases, hacker groups are changing the game and expanding their footprints of destruction with sophisticated tools to infiltrate operations, attack critical applications and gain access to data. Ralf Sydekum of F5 Networks believes that the EU's General Data Protection Regulation (GDPR) might lead to better data management and greater transparency, and will force organisations to improve their security. On the other hand, businesses that ignore requirements for transparency and fairness will suffer severe reputational and financial consequences